If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(b + 6) = 6(b + -36) Reorder the terms: 4(6 + b) = 6(b + -36) (6 * 4 + b * 4) = 6(b + -36) (24 + 4b) = 6(b + -36) Reorder the terms: 24 + 4b = 6(-36 + b) 24 + 4b = (-36 * 6 + b * 6) 24 + 4b = (-216 + 6b) Solving 24 + 4b = -216 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 24 + 4b + -6b = -216 + 6b + -6b Combine like terms: 4b + -6b = -2b 24 + -2b = -216 + 6b + -6b Combine like terms: 6b + -6b = 0 24 + -2b = -216 + 0 24 + -2b = -216 Add '-24' to each side of the equation. 24 + -24 + -2b = -216 + -24 Combine like terms: 24 + -24 = 0 0 + -2b = -216 + -24 -2b = -216 + -24 Combine like terms: -216 + -24 = -240 -2b = -240 Divide each side by '-2'. b = 120 Simplifying b = 120
| x^2+42=16x | | 10+-2x=2 | | sin(0)ln(0)= | | 6x+4x-20=0 | | .08=-.015XY | | .03t+.004=.72t-1.8 | | -6sin(6x)=0 | | 10x^2+31x+3=0 | | 5m^2+mn+12n^2=0 | | 2(x+3)=180 | | 4(x+3)-7=6x-2(-2+x) | | 5(x+2)=4x+16 | | 3x^2+14=-43 | | -2z-3z=5z+7-6z | | 19+3(6-7)=18x-2 | | -6(w+4)-(7w-9)=-14w | | q=3+6g | | 12+-3x=0 | | 5(5+6x)=25 | | (3+-z)=5 | | -13x+8+8x=-9x-22 | | h=-16t^2-17t+120 | | z^2+8z-20= | | 6x^5+35x^4+36x^3-79x^2-96x+18=0 | | -.20x+1=-7 | | 4(4+5x)=216 | | 21.54=30+18x | | 2x+10-(7x-(12(x-1)-5))=5(x-3) | | 7p-(3p+4)=-2p-1+10 | | 30+18x=21.54 | | 20x^3+100x^2=0 | | 34x-16+15x^2=0 |